ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA DI INDONESIA - Mesi Mukhlisiana; idris Idris; Melti Roza Adry (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to determine and analyze the effect of wages, education and health on labor produkctivity. Wage are measured using the provincial minimum wage data, education is measured using data on the percentafe of the populationaged 15 years and over who have a high school/vocational education and Indonesia tertiary education and health is measured using data on the percentage of the population experiencing pain complaints. This type of research is descriptive and associative research that describes the research variales amd find out whether there is influencer between the independent variable and the dependent variabel. The type of data in this research is panel power from 2013-2017 in Indonesia. Analysis of the data used in this study is the Panel Regression Analysis. The results of this study indicate that (1) Wage have significant effect on the productivity of Indonesia workers, (2) Education does not  have a significant effect on the productivity of Indonesia workers, (3) Health has a significant effect on the productivity of Indonesia workers, (4) Together education and health wages have a significant effect on the productivity of the Indonesia workforce.